The business blockchain : promise, practice, and application of the next Internet technology - Mougayar, William (Online access with DDA: Askews (Economics), 2016)
The definitive pioneering blueprint covering the what, why and how of the blockchain. Blockchains are new technology layers that rewire the Internet and threaten to side-step older legacy constructs and centrally served businesses. At its core, a blockchain injects trust into the network, cutting off some intermediaries from serving that function and creatively disrupting how they operate. Metaphorically, blockchains are the ultimate non-stop computers. Once launched, they never go down, and offer an incredible amount of resiliency, making them dependable and attractive for running a new generation of decentralized services and software applications. The Business Blockchain charts new territory in advancing our understanding of the blockchain by unpacking its elements like no other before. William Mougayar anticipates a future that consists of thousands, if not millions of blockchains that will enable not only frictionless value exchange, but also a new flow of value, redefining roles, relationships, power and governance. In this book, Mougayar makes two other strategic assertions. First, the blockchain has polymorphic characteristics; its application will result in a multiplicity of effects. Second, we shouldn't ask ourselves what problems the blockchain solves, because that gives us a narrow view on its potential. Rather, we should imagine new opportunities, and tackle even more ambitious problems that cross organizational, regulatory and mental boundaries. Drawing on 34 years of technology industry experience as an executive, analyst, consultant, entrepreneur, startup mentor, author, blogger, educator, thought leader and investor, William Mougayar describes a future that is influenced by fundamental shifts brought by blockchain technology as the catalyst for change. William Mougayar has been described as the most sophisticated blockchain business thinker. He is a blockchain industry insider whose work has already shaped and influenced the understanding of blockchain for people around the world, via his generous blogging and rigorous research insights. He is a direct participant in the crypto-technology market, working alongside startups, entrepreneurs, pioneers, leaders, innovators, creators, enterprise executives and practitioners; in addition to being an investor, advisor, and board member in some of the leading organizations in this space, such as the Ethereum Foundation, OpenBazaar and Coin Center. Just as the Internet created new possibilities that we didn't foresee in its early years, the blockchain will give rise to new business models and ideas that may still be invisible. Following an engaging Foreword by Vitalik Buterin, this book is organized along these 7 chapters: 1. What is the Blockchain' 2. How Blockchain Trust Infiltrates 3. Obstacles, Challenges & Mental Blocks 4. Blockchain in Financial Services 5. Lighthouse Industries & New Intermediaries 6. Implementing Blockchain Technology 7. Decentralization as the Way Forward The Business Blockchain is an invitation for technologists to better understand the business potential of the blockchain, and for business minded people to grasp the many facets of blockchain technology. This book teaches you how to think about the blockchain.